Day Visit to Yosemite National Park - Watkins, Howard::::::::: (1985)
Howard Watkins and Christine Watkins at Yosemite Tunnel Overlook with Yosemite Falls and Half Dome in background Six-person tent set up by picnic table on concrete slab;